Rockburst Prediction on the Superimposed Effect of Excavation Accumulation Energy and Blasting Vibration Energy in Deep Roadway - Qingwen Li; Ben Xiang (Shock and Vibration)
In deep mining, much elastic energy is stored in rock mass due to the high geostress. Rockburst will be induced by accumulated energy during excavation. Meanwhile, because of blasting vibration energy in the host rock, there will be an obvious superimposed effect on the probability and intensity of rockburst. To explore the most reasonable and effective method for understanding rockburst problem under blasting, a deep roadway of Sanshandao gold mine was studied. On the basis of in situ geostress data, the accumulated energy of three-centered arch roadway after quasi-static excavation was derived. Then, a series of in situ blasting vibration were monitored, and the blasting vibration energy was calculated by employing the equivalent theory of elastic vibration boundary. Finally, the tendentiousness of rockburst was evaluated qualitatively with the superimposed energy. The results indicated that the disaster-driven energy was increased by 45.1% and 28.2% on different places of roadway. Also, the probability and intensity of rockburst would be raised.